2012
DOI: 10.1016/s1995-7645(12)60004-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiplasmodial effect of ethanolic extracts of traditional medicinal plant Ocimum species against Plasmodium falciparum

Abstract: The ethanolic leaf extracts of O. sanctum possess lead compounds for the development of antiplasmodial drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…1). The IC 50 value (21.14 µg mLG 1 ) of the stem/root aqueous extract was found to be lower, thus was more active against P. falciparum relative to the root (IC 50 >100 µg mLG 1 ) and stem (IC 50 = 83.53 µg mLG 1 ) separately as reported by Inbaneson et al (2012). This could be due to the combined effects of the phytochemicals present in the roots and those in the stem.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…1). The IC 50 value (21.14 µg mLG 1 ) of the stem/root aqueous extract was found to be lower, thus was more active against P. falciparum relative to the root (IC 50 >100 µg mLG 1 ) and stem (IC 50 = 83.53 µg mLG 1 ) separately as reported by Inbaneson et al (2012). This could be due to the combined effects of the phytochemicals present in the roots and those in the stem.…”
Section: Resultsmentioning
confidence: 63%
“…The aqueous extract of the leaves with fruits of P. amarus gave an IC 50 value of 13.96 µg mLG 1 . The anti-plasmodial activity of the leaves of P. amarus has been reported by Inbaneson et al (2012) against P. falciparum. Their results indicated that the ethanolic leaf extract showed an IC 50 of 94.19 µg mLG 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kultur P. falciparum menggunakan lempeng sumur 24, masing-masing sumur berisi 1 mL kultur yang telah disinkronisasi menggunakan sorbitol 5% dengan parasitemia ± 1% dan hematokrit 5% dalam medium RPHS. Medium RPHS kemudian diganti dengan medium RPHS yang mengandung ekstrak air kayu akway berbagai konsentrasi (1 sampai 1x10 -7 mg/mL) (Inbaneson et al, 2012;Fidock et al, 2004).…”
Section: Metode Penelitianunclassified
“…The main chemical constituents of O. sanctum are oleanolic acid, ursolic acid, rosmarinic acid, eugenol, carvacrol, linalool, and β-caryophyllene. [34] The antiviral activity of eugenol has been reported. Ocimum extracts are used in ayurvedic remedies for common colds, headaches, stomach disorders, inflammation, heart disease, various forms of poisoning, and malaria.…”
Section: Introductionmentioning
confidence: 99%